Submucosal fat accumulation in human colorectal tissue and its association with abdominal obesity and insulin resistance. Issue 7 (August 2018) - Wada, Seriko; Yasunaga, Yuichi; Oka, Kazumasa; Dan, Naoki; Tanaka, Eri; Morita, Kaori; Masuda, Eriko; Yanagawa, Kazunori; Matsumoto, Hitoshi; Yoshioka, Shinichi; Tsujie, Masaki; Inui, Yoshiaki; et al.
Background: In addition to visceral fat, peripheral ectopic fat accumulation is suggested to play a role in the pathophysiology of metabolic syndrome, which is known to be associated with not only cardiovascular diseases and type 2 diabetes mellitus but also colorectal cancer. Objective: This study aims to clarify whether there is ectopic fat accumulation in human colorectal tissue in association with metabolic syndrome or its components such as abdominal obesity and insulin resistance. Methods: Lipid contents of colorectal tissue were measured in 27 patients with colorectal polyp excised endoscopically. In addition, lipid droplets were immunohistochemically estimated using anti-perilipin antibody in 32 patients with colorectal cancer resected surgically. Results: Increasing tissue triglyceride/phospholipid ratio was associated with increasing body mass index, fasting plasma insulin level and homeostasis model assessment as an index of insulin resistance (HOMA-IR), and also decreasing serum adiponectin level. Lipid droplets were observed in the submucosal region of colorectal tissue. The amount of lipid droplets was associated with increasing body mass index, waist circumference and visceral fat area. Conclusion: This study showed the presence of submucosal fat accumulation in human colorectal tissue and its association with abdominal obesity and insulin resistance.